2015
DOI: 10.5888/pcd12.150199
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Improve the Integration of Community Health Workers Into Health Care Teams: “A Little Fish in a Big Pond”

Abstract: IntroductionThe Patient Protection and Affordable Care Act acknowledges the value of community health workers (CHWs) as frontline public health workers. Consequently, growing attention has been placed on promoting CHWs as legitimate partners to provide support to health care teams and patients in the prevention, management, and control of chronic disease, particularly among diverse populations and high-need individuals.MethodsUsing a mixed-methods research approach, we investigated the integration of CHWs into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 20 publications
3
37
0
Order By: Relevance
“…Previous studies share lessons learned from integrating CHWs into a team-based practice, [27][28][29][30][31] but only 1 included descriptions of the preimplementation decision making that led to piloting the CHW model. Their results echoed themes from our study, including having an awareness of the CHW model and influential champions, and building institutional support through documented return on investment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies share lessons learned from integrating CHWs into a team-based practice, [27][28][29][30][31] but only 1 included descriptions of the preimplementation decision making that led to piloting the CHW model. Their results echoed themes from our study, including having an awareness of the CHW model and influential champions, and building institutional support through documented return on investment.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Researchers have explored the experience of CHWs with integration into care teams and examined how health care delivery systems might be Elizabeth A. Rogers, MD,MAS 1 designed to effectively embed them. [27][28][29][30][31] Experts have outlined implementation barriers (fragmented and disease-specific interventions, lack of clear work protocols, high turnover, variable performance, and a history of low-quality evidence), but argue that these barriers can be overcome through established standards to ensure a skilled CHW workforce, clearly defined roles, concrete implementation strategies, and an expanded scope of reimbursable services to include their services. 5,6,25,26,32 Little research exists on whether these strategies are sufficient for wide adoption of CHWs within primary care and how clinics make decisions about this adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Although research on CHW integration is limited, our findings suggest Nebraska workplace environments are favorable for CHW integration. In a mixed methods study examining CHW perspectives, communication was identified as beneficial to the well-being of the CHW and to the care team and patient [1]. In particular, CHWs cited important facilitators to CHW integration include having consistent team meetings, training inside and outside of the organization, and ability to stay connected with the community and with other CHWs.…”
Section: Discussionmentioning
confidence: 99%
“…Although serving a vital role in connecting patients to the healthcare system, research has shown that CHWs have largely been structurally excluded from major aspects of the healthcare system, including clear roles and workflows within care teams, participation in team meetings and access to electronic health records (EHRs) 5 6. Conversely, when CHWs are integrated into the healthcare system, they are effective at improving healthcare outcomes for patients 6–8. Effective integration of CHWs into the care team allows CHWs to share vital perspectives of the home environment to clinic-based healthcare providers who may have little or no insight into patient’s living situation and psychosocial surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…Effective integration of CHWs into the care team allows CHWs to share vital perspectives of the home environment to clinic-based healthcare providers who may have little or no insight into patient’s living situation and psychosocial surroundings. By expanding community–clinic linkages and connecting CHWs with the healthcare system, CHWs are better able to support both the patients and providers in forming an effective patient-centred care team 6 9…”
Section: Introductionmentioning
confidence: 99%